Cooperative learning (CL) as 21st century’s teaching method in improving english proficiency among primary school student: teachers’ perception - Mahbib, Umi Kalthom; Esa, Ahmad; Mohamad, Nurul Haerani; Mohd Salleh, Berhan (Universiti Putra Malaysia Press, 2017)
Cooperative learning (CL) as a 21st-century classroom teaching method has begun to be viewed as a form of active learning in Malaysia. Although CL has been applied and successfully implemented abroad, it is still considered difficult to put into practice among primary school teachers in Malaysia for improving English among primary school students. Primary school teachers are more comfortable with conventional teaching methods including using the national language, Bahasa Malaysia. In order to implement CL successfully, teachers require knowledge of CL, its features and terms and how it functions in classrooms. This qualitative study examined 10 primary school teachers’ from the southern zone of Peninsular Malaysia on their understanding of CL and factors perceived to affect its implementation. Using Johnson and Johnson’s (1994) features of CL and Bain, Lancaster and Zundans’ (2009) list of CL terms as a framework for analysis, we found that the teachers’ level of CL knowledge shaped their perception of the factors affecting its implementation in the classroom. However, more research is needed to explain how teachers’ knowledge of CL can shape what teachers perceive as barriers to effective implementation that affect the success of CL in practice.